Fettabsaugung – Die einzige Therapie zur Reduktion der Fettgewebehypertrophie beim Lymphödem - Brorson, H. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2012)
The various types of treatment of lymphedema are under discussion and there has been some controversy regarding liposuction for lymphedema. Although it is clear that conservative therapies such as complex decongestive therapy (CDT) and controlled compression therapy (CCT) should be tried in the first instance, options for the treatment of late-stage lymphedema that is not responding to such treatment is not so clear. Improvements in technique, patient preparation, and patient follow-up have led to a greater and a wider acceptance of liposuction as a treatment for lymphedema. This paper outlines the benefits of using liposuction and presents the evidence to support its use.
Keywords: liposuction; lymphedema; adipose tissue; upper limb; lower limb; lymphatics